Formation of Yolk-Shelled Ni-Co Mixed Oxide Nanoprisms with Enhanced Electrochemical Performance for Hybrid Supercapacitors and Lithium Ion Batteries - Yu, Le (2015)
Yolk-shelled particles with tailored physical and chemical properties are attractive for electrochemical energy storage. Starting with metal acetate hydroxide with tetragonal prism-like shapes, yolk-shelled Ni–Co mixed oxide nanoprisms with tunable composition have been prepared by simple thermal annealing in air. It is found that the yolk-shelled structure is formed due to the fast thermally driven contraction process. With the favorable porous structure and composition, these yolk-shelled Ni–Co oxide particles manifest greatly enhanced electrochemical properties when evaluated as electrodes for both hybrid supercapacitors and lithium ion batteries. In particular, the resultant Ni0.37Co oxide sample delivers very high specific capacitance of over 1000 F g−1 at a current density of 10 A g−1 with remarkably high capacitance retention of 98% after 15 000 cycles.